Suicidal Death due to Hanging (Delta Medical College Journal, 2017)
Background: Hanging is always suicidal unless otherwise proved. It is a form of violent asphyxial death. It produces painless death for the victims so that it is a widely practiced method of suicide. In Bangladesh hanging is one of the commonest methods of suicide.Objective: The objective of this study was to find out socio-demographic characteristics of victims, common ligature materials used by victims and post-mortem findings.Materials and method: A retrospective cross sectional study was done in Dhaka Medical College Mortuary during the period of January 2009 to January 2010. During this period data were collected from 2133 cases of medicolegal autopsies by purposive sampling.Results: A total of 2133 medicolegal autopsies were analyzed of which 78 (3.65%) were deaths due to hanging. Out of these 78 cases maximum 37 (47.44%) deaths due to hanging were in the age group of 21-30 years. Majority of the cases (48; 61.54%) were observed in females. Majority (32; 41.03%) of victims had used Dopatta (orna) as a ligature material. Cyanosis of fingertips and nail beds was the commonest (75; 96.15%) findings in cases of asphyxial death due to hanging.Conclusion: Suicidal hanging is observed in this study mostly within the young age group ranging from 21-30 yrs. So, awareness at the level of family and community should be raised to improve personal and social relation in every sphere. The factors provoking an individual for an attempt to suicide should also be investigated for its prevention.Delta Med Col J. Jul 2017 5(2): 89-93